Relationship Between Dendrometric of Mango Trees (Mangifera indica L.) and Geographic Variations on Critical Land in Jombang Regency - Muchamad Suhada Nasrulloh; Zulfikar Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the dendrometric relationship of mango trees to various elevation variations on critical land. The research method uses a parametric regression approach and the data analysis tool uses Excel. The dendrometric variables analyzed were canopy area, number of branches, and stem diameter. The results of the analysis showed that the correlation value between elevation and strong canopy area (r = 0.64), with a low number of branches (r = 0.38) and with a very strong trunk diameter (r = 0.83). The regression equation was obtained in a linear form from the relationship between elevation and canopy area (R2 = 0.40) with the regression equation Y = 0.06x + 24.8.. and stem diameter (R2 = 0.68) with the regression equation Y = 1.165x + 21.84, and nonlinear with the number of branches (R2 = 0.282) with the regression equation y = 0.86x5 – 18.79x4 + 157.6.x3 – 634.3.x2 + 1231x – 869.5. This shows that the canopy area and the trunk diameter of mango trees have a strong and linear correlation, except for the number of branches